Vascular-targeted TNFα and IFNγ inhibits orthotopic colorectal tumor growth. Issue 1 (December 2016) - Shen, Jing; Li, Zhi; Li, Long; Lu, Lan; Xiao, Zhan; Wu, William; Zhang, Lin; Li, Ming; Hu, Wei; Chan, Kam; Cho, Chi
Abstract Background Tumor necrosis factor alpha (TNFα) and interferon gamma (IFNγ) were originally identified to show potent anti-tumor activity and immunomodulatory capability. Unfortunately, several clinical studies of relevant cancer therapy did not observe significant response in maximum tolerated dose whether given alone or in combination. We have identified a tumor vasculature homing peptide (TCP-1 peptide) which targets only the vasculature of colorectal tumors but not normal blood vessels in animals and humans. In the current study, the antitumor effect of TCP-1/TNFα and TCP-1/IFNγ alone or in combination was studied in orthotopic colorectal tumor model. Methods TCP-1/TNFα and TCP-1/IFNγ recombinant proteins were prepared and i.v. injected to study the in vivo anticancer effect in orthotopic colorectal tumor model. Tumor apoptosis was determined by TUNEL staining and cleaved caspase-3 immunofluorescent staining. Tumor infiltrating lymphocytes were analyzed by immunofluorescent staining and flow cytometry. Western-blot was performed to examine the expression of proteins. Cell apoptosis was measured by Annexin V/PI flow cytometry. Results Targeted delivery of TNFα or IFNγ by TCP-1 peptide exhibited better antitumor activity than unconjugated format by inducing more tumor apoptosis and also enhancing antitumor immunity shown by increased infiltration of T lymphocytes inside the tumor. More importantly, combination therapy of TCP-1/TNFα and TCP-1/IFNγ synergistically suppressed tumor growth and alleviated systematic toxicity associated with untargeted therapy. This combination therapy induced massive apoptosis/secondary necrosis in the tumor. Conclusions Taken together, our data demonstrate TCP-1 is an efficient drug carrier for targeted therapy of colorectal cancer (CRC). TCP-1/TNFα combined with TCP-1/IFNγ is a promising combination therapy for CRC.